2022
DOI: 10.1007/s13555-022-00745-7
|View full text |Cite
|
Sign up to set email alerts
|

The Tuberculosis Positive Conversion Rate Among Psoriasis Patients Treated with Adalimumab and Secukinumab: A Single-Center Retrospective Study in China

Abstract: Introduction The tuberculosis (TB) positive conversion rate among psoriasis patients who received biologics has been reported worldwide, particularly in regions with low TB risk. Nonetheless, the TB-related safety of biologics such as adalimumab and secukinumab remains elusive in areas with high TB risk. According to the World Tuberculosis Report 2021, China is the country with the second highest TB burden, but data on TB conversion are also limited. Thus, we performed a retrospective, single-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…[29] In various case series, no LTBI reactivation was observed in patients with LTBI who used SEC due to psoriasis and did not receive anti-TB prophylaxis. [30][31][32][33] To our knowledge, active TB infection under SEC treatment has been reported in only one case in the literature, a 19-year-old male from Vietnam (a country with a high TB burden) who used SEC for peripheral spondyloarthritis. The patient's symptoms improved with discontinuation of SEC and anti-TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[29] In various case series, no LTBI reactivation was observed in patients with LTBI who used SEC due to psoriasis and did not receive anti-TB prophylaxis. [30][31][32][33] To our knowledge, active TB infection under SEC treatment has been reported in only one case in the literature, a 19-year-old male from Vietnam (a country with a high TB burden) who used SEC for peripheral spondyloarthritis. The patient's symptoms improved with discontinuation of SEC and anti-TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been confirmed that receiving TNFi, particularly anti-TNFα monoclonal antibodies, was one of the high-risk groups for developing active TB [ 18 ]. In 2022, our team also showed that two patients with psoriasis (2.17%, 2/92) with baseline IGRA negative results suffered active TB during follow-up in the high-burden region [ 19 ]. Previous research has indicated that prophylactic therapy can reduce the risk of developing active TB in such a high-risk group, and isoniazid monotherapy is 60–90% effective for 6–12 months [ 15 ].…”
Section: Discussionmentioning
confidence: 99%